Essays on last mile logistics alliances and the finite horizon joint replenishment problem - Jagannathan, Madhav (Nanyang Technological University, 2023)
The first and second essay in the thesis focus on analyzing and developing mechanisms for implementing collaboration between logistic service providers (LSPs) undertaking last-mile delivery of ecommerce parcels and to share cost savings generated through collaboration between the LSPs. These works were motivated by some industry workshops organized by Volvo and supported by Enterprise Singapore/Media Development Authority and insights garnered from practicing senior managers of logistics companies during the workshop. The primary questions these two pieces of work address are: 1) Broadly, what are the mechanisms for structuring the logistics alliances among last-mile delivery players to achieve greater system efficiency and reduce CO2 emissions? 2) How should a bidding/offering mechanism be designed to ensure the savings allocation based on cooperative mechanisms are achieved in an arms-length system of sharing delivery workload? One essay is on a stylized problem involving delivery between two points (in either direction) with the objective of minimizing empty backhauls. The other essay addresses the problem of deliveries to several customers in a delivery route.